Utilization Of Accounting Information Systems, Human Resource Competencies, Government Accounting Standards On The Quality Of Local Government Financial Statements - Dian Nurazizah; Fatima Azahra; Wildaniyahtul Jannah; Moh. Yudi Mahadianto; Nelia Fariani (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
The local government financial report is a form of accountability report for the implementation of the Regional Revenue and Expenditure Budget that can be calculated with money. This study aims to assess the effect of utilization of accounting information systems, human resource competencies, and government accounting standards on the quality of local government financial reports. In this study, researchers used a quantitative descriptive approach. The information collection method used is through a questionnaire. The number of samples was 95 respondents who were determined using purposive testing techniques. Data analysis was performed with multiple linear regression models with data quality testing and classical assumption tests. The results of this study indicate that the utilization of accounting information systems, human resource competencies, and the application of government accounting standards have a significant effect on the quality of local government financial reports.